2021
DOI: 10.3390/polym13111843
|View full text |Cite
|
Sign up to set email alerts
|

Using P(Pressure)-T(Temperature) Path to Control the Foaming Cell Sizes in Microcellular Injection Molding Process

Abstract: Microcellular injection molding technology (MuCell) using supercritical fluid (SCF) as a foaming agent is one of the important green molding solutions for reducing the part weight, saving cycle time, and molding energy, and improving dimensional stability. In view of the environmental issues, the successful application of MuCell is becoming increasingly important. However, the molding process encounters difficulties including the sliver flow marks on the surface and unstable mechanical properties that are caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Although the combined use of GCP and a mould temperature control system can successfully eliminate silver marks, the use of GCP alone increases the solid skin thickness, which compromises the part weight reduction, while the individual use of a mould temperature control system increases the size of the cells and contributes to an uneven distribution of cells in the MuCell ® parts. Furthermore, it was found that the critical parameters in the P-T control system, such as gas pressure holding time, relief time, and the mould cooling speed result in different cell morphologies [ 67 ]. Longer relief times and faster cooling speeds, which can be induced by controlling the holding time, originated thick skin thicknesses and small cell sizes.…”
Section: Silver Marks and Solid Skin Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the combined use of GCP and a mould temperature control system can successfully eliminate silver marks, the use of GCP alone increases the solid skin thickness, which compromises the part weight reduction, while the individual use of a mould temperature control system increases the size of the cells and contributes to an uneven distribution of cells in the MuCell ® parts. Furthermore, it was found that the critical parameters in the P-T control system, such as gas pressure holding time, relief time, and the mould cooling speed result in different cell morphologies [ 67 ]. Longer relief times and faster cooling speeds, which can be induced by controlling the holding time, originated thick skin thicknesses and small cell sizes.…”
Section: Silver Marks and Solid Skin Formationmentioning
confidence: 99%
“…Chen et al [59] developed a novel pressure-temperature (P-T) contro bining a GCP and mould temperature control system together in the mi tion moulding process, obtaining parts with small and uniform cells and Although the combined use of GCP and a mould temperature control sys fully eliminate silver marks, the use of GCP alone increases the solid skin compromises the part weight reduction, while the individual use of a mo control system increases the size of the cells and contributes to an uneve cells in the MuCell ® parts. Furthermore, it was found that the critical par T control system, such as gas pressure holding time, relief time, and th speed result in different cell morphologies [67]. Longer relief times an speeds, which can be induced by controlling the holding time, originated nesses and small cell sizes.…”
Section: Silver Marks and Solid Skin Formationmentioning
confidence: 99%
“…Microcellular injection technology [ 24 , 25 , 26 ] is a special process to overcome some problems that the conventional injection molding cannot. Most of the microcellular foam plus GCP technology [ 27 , 28 ] emphasizes improving surface roughness problems.…”
Section: Introductionmentioning
confidence: 99%
“…Foaming also plays a significant role in the packing stage, resulting in shrinkage reduction, warpage minimization, and the elimination of residual stresses, etc. Studies on the process characteristics of MuCell ® and the associated molded-part properties have been reported earlier [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Despite its advantages, MuCell ® also faces technological difficulties leading to hesitation in its further application.…”
Section: Introductionmentioning
confidence: 99%
“…A high foaming density, fine cell size, and uniform size distribution seem to be required to in order to fulfill the formed sole properties. Thus, in this study we extend our foaming control experiences in MuCell ® of thermoplastics [ 17 , 18 , 19 , 20 , 21 ], namely, gas counter pressure and mold-temperature control constituting the so-called P (pressure)-T (temperature) path [ 21 ], to see if it also works for thermoplastic elastomers (such as TPU). Relevant processing parameters including SCF dosage, injection speed, mold temperature, gas counter pressure, and gas holding time on foaming cell size and the associated size distribution were investigated in detail.…”
Section: Introductionmentioning
confidence: 99%